'We don't have to go and see a special person to solve this problem': Trauma, mental health beliefs and processes for addressing 'mental health issues' among Sudanese refugees in Australia. (February 2016) - Savic, Michael; Chur-Hansen, Anna; Mahmood, Mohammad Afzal; Moore, Vivienne M
Background: The impact of trauma on refugee mental health has been a particular focal point for research and treatment in Western contexts, despite uncertainty about the degree to which this corresponds with refugees' needs, mental health beliefs and healing mechanisms. Aims: This study explored the mental health beliefs of resettling Sudanese refugees in Australia. Methods: In-depth qualitative interviews were conducted with Sudanese community representatives and with a range of health and social work professionals who were not necessarily Sudanese. Results: The concept of trauma was not universally considered to be salient for Sudanese refugees. Key informants, especially those in refugee-oriented services, emphasised stoicism and a desire to move forward and questioned the appropriateness of Western psychological therapies. Processes that exist within the family and the Sudanese community to deal with stressors like loss, grief and social isolation were explained. Conclusion: Dialogue between services and community members is needed to ensure responses to refugee mental health are sensitive to the diversity of needs and mental health beliefs of refugees. This will enable workers to ascertain how individual refugees understand their experiences of distress or sadness and to determine whether community strategies and/or professional responses are appropriate.